PENGARUH MODEL PEMBELAJARAN INTEGRATIF DAN MODEL PEMBELAJARAN EXPERIENTIAL TERHADAP KETERAMPILAN MENYIMAK BAHASA INGGRIS MAHASISWA - Agus Supriyadi (Universitas Khairun, 2021)
The aim of this research is to find the effect of learning model on students’ English listening skill. The research was conducted at the English Study Education Program, Language and Art Department, Faculty of Teachres Training and Education of Universitas Khairun, Ternate. The research method is an experiment with the quantitative approach, using factorial design of 2 x 2. The sample size are 32 students. The research result showed that: (1) English listening skills of the students’ who taught with integrative learning models was higher than the student who taught with the experiential models; (2 There is an influence of interaction between the learning model on students’ English listening skills; This is due to the fact that the experiential models is more appropriate for students who have a special character.